Development of problem-based science practicum instructions of Junior High School Students - Rahmat, Irwandi; Chanunan, Skonchai; Yani, Ahmad (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2023)
This study aims to develop problem-based science practicum instructions intended for grade VIII junior high school / MTs students in the odd semester. The problem-based approach was chosen because it has been proven effective in improving students' critical thinking and problem solving skills. This research uses the 4D method which includes the Define, Design, Develop and Dissaminate stages. The results of this study indicate that the problem-based practicum instructions developed are valid, practical and effective. The validity value is 4.2 which means that the problem-based practicum instructions are included in the valid criteria. The practicality value is 4.6 which means that the problem-based practicum instructions are classified as practical criteria. The problem-based practicum instructions developed have also been classified as effective by looking at the results of positive responses from students which reached 84.8%. The final product resulting from this research is expected to be a reference for teachers in teaching science with a problem-based approach, so as to improve the quality of science learning in schools. Keywords: practical guidelines, science learning, junior high students